Risk factors for peptic ulcer disease: a population based prospective cohort study comprising 2416 Danish adults. Issue 2 (1st February 2003) - Rosenstock, S; Jørgensen, T; Bonnevie, O; Andersen, L
Abstract : Background: No population based prospective cohort study has previously assessed the impact of multiple risk factors, including Helicobacter pylori infection, on the incidence of peptic ulcer disease (PUD). Aims: To identify risk factors for PUD and estimate their relative impact on ulcer incidence. Subjects: Random sample of 2416 Danish adults with no history of PU. Methods: Sample members were interviewed in 1982 and 1994. PUs diagnosed within the observation period were verified through medical records. Information on psychosocial factors, lifestyle practices, and medication was obtained from a questionnaire completed at study entry. H pylori infection status was determined by ELISA. Results: The main risk factors for PUD were H pylori infection (odds ratio 4.3 (95% confidence interval 2.2; 8.3)), tobacco smoking (3.8 (1.7; 9.8)), and use of minor tranquillisers (3.0 (1.4; 6.6)). Intake of non-steroid anti-inflammatory drugs did not affect the incidence of PUD (0.4 (0.1; 2.3)). In those with increased antibodies to H pylori, tobacco smoking (12.7 (2.8; 56.8)) and intake of spirits (2.4 (1.1; 5.4)) increased the risk of PUD whereas moderate leisure time physical activity (0.3 (0.2; 0.7)) protected against PUD. Conclusions: Tobacco smoking and H pylori infection are the main risk factors for PUD in Danish adults. Physical activity may protect against PUD in those infected with H pylori .